2010
DOI: 10.1002/jssc.201000578
|View full text |Cite
|
Sign up to set email alerts
|

Sicilian lemon oil: Composition of volatile and oxygen heterocyclic fractions and enantiomeric distribution of volatile components

Abstract: A total of 92 samples of Sicilian lemon oils (Citrus limon (L.) Burm. f.) produced from September 2008 to June 2009, industrially cold-pressed by different extraction techniques (Brown Oil Extractor and Food Machinery Corporation), were analyzed by GC-flame ionization detector (FID) and GC/MS-LRI to investigate the volatile fraction; by RP-HPLC/PDA to determine the non-volatile components and by enantio-GC-FID to determine the enantiomeric ratios of 12 volatile components. This study provides a detailed invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Oxygen-containing heterocyclic metabolites, consisting of coumarins, furanocoumarins, and polymethoxylated flavones, were present in the oil at 4.9% (w/v) before the peel started yellowing (70 mm ED) and then decreased slightly to 4.1% (w/v) in oil obtained from mature fruit (100 mm ED; Table I). This is consistent with prior studies (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). Carotenoids had been described as minor components of cold-pressed Citrus oils (Dugo et al, 2006) but were undetectable in our microcapillary-collected grapefruit oil samples (Table I).…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedsupporting
confidence: 92%
See 2 more Smart Citations
“…Oxygen-containing heterocyclic metabolites, consisting of coumarins, furanocoumarins, and polymethoxylated flavones, were present in the oil at 4.9% (w/v) before the peel started yellowing (70 mm ED) and then decreased slightly to 4.1% (w/v) in oil obtained from mature fruit (100 mm ED; Table I). This is consistent with prior studies (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). Carotenoids had been described as minor components of cold-pressed Citrus oils (Dugo et al, 2006) but were undetectable in our microcapillary-collected grapefruit oil samples (Table I).…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedsupporting
confidence: 92%
“…Studies on the nonvolatile constituents of Citrus essential oil began in the 1960s (for review, see Dugo et al, 2009), but reliable quantifications for grapefruit were not reported until much later (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). All of these studies used cold-pressed grapefruit oil for phytochemical and chemometric analyses.…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedmentioning
confidence: 99%
See 1 more Smart Citation
“…The SH profiles, in lemon and bergamot oils, are very similar. The qualitative differences are related to the presence, in one of the two oils, of minor constituents; in particular, the absence of germacrene A and D in lemon oil must be highlighted, because these compounds have been reported before in this oil‐type . The main % differences are related to the different proportions of the three main compounds, and to the different percentages of bicyclogermacrene, tr‐β ‐farnesene, α ‐humulene and cis‐γ ‐bisabolene.…”
Section: Resultsmentioning
confidence: 97%
“…The last three lines of the table report information relative to the experimental absolute content of SH expressed as g/100 g of essential oil, SH% ranges (without standardization) reported in the literature, and the experimental % value (without standardization) found …”
Section: Resultsmentioning
confidence: 99%